A Comparative Study of Melissa officinalis Leaves and Stems Ethanolic Extracts in terms of Antioxidant, Cytotoxic, and Antiproliferative Potential. (16th May 2018) - Moacă, Elena-Alina; Farcaş, Claudia; Ghiţu, Alexandra; Coricovac, Dorina; Popovici, Ramona; Cărăba-Meiţă, Nela-Loredana; Ardelean, Florina; Antal, Diana Simona; Dehelean, Cristina; Avram, Ştefana
Abstract : Melissa officinalis L. has attracted an increased interest in recent years due to its multiple pharmacological effects. This study aimed to compare two M. officinalis ethanolic extracts, obtained from leaves and stems, with regard to their antioxidant activity, total phenolic content, and cytotoxic effects. M. officinalis ethanolic extracts showed a very good antioxidant activity in the DPPH test, correlated with the content in total phenols: higher in the case of M. officinalis from leaves extract (32.76 mg GAE/g) and lower for M. officinalis from stems extract (8.4 mg GAE/g). The lemon balm extracts exerted a cytotoxic effect on breast cancer cells (MDA-MB-231) even at low concentrations (100 μ g/mL), whereas, in the case of healthy HaCat cells, M. officinalis leaves extract only displayed cytotoxicity at much higher concentrations (500 and 1000 μ g/mL) and M. officinalis stems extracts were highly cytotoxic (starting at 100 μ g/mL). In addition, the extracts exerted inhibitory effects on cell migration and proliferation. These results provide information that confirms the high potential of M. officinalis as a source of chemopreventive agents. Moreover, these data can be considered a solid background for further in vivo studies involving mice bearing breast tumors.